Supply Chain Management Strategies on Oil and Gas Companies Performance in Nigeria - Clement Aliu Ogbaini (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Nigeria's oil and gas sector, a significant contributor to the country's economy, accounts for 92% of export value and 5.5% of GDP. However, challenges such as supply chain inefficiencies hinder its optimal performance. This study investigates the impact of supply chain management strategies on the performance of Nigerian oil and gas companies. Adopting a mixed-method research design, the study utilized Taro Yamane’s formula to determine a sample size of 100 respondents, employing stratified random sampling to select participants from the upstream, midstream, and downstream operational strata of the oil and gas industry. Data collection was conducted through structured questionnaires and interviews, while data analysis employed descriptive statistics, including frequency distributions, percentages, means, and standard deviations. Hypotheses were tested using chi-square statistics to establish relationships and validate findings. The results revealed that the integration of advanced technologies, third-party logistics providers, and effective risk management significantly enhances supply chain performance in the oil and gas sector. The study recommends the adoption of advanced data analytics, artificial intelligence (AI), blockchain technology, the Internet of Things (IoT), and enterprise resource planning (ERP) systems for data-driven decision-making, risk prediction, operational optimization, and demand forecasting. Additionally, oil and gas companies should conduct comprehensive risk assessments, develop robust business continuity plans (BCPs), and implement regular drills and simulations to ensure operational resilience during disruptions. This study contributes to the body of knowledge on supply chain management strategies in the oil and gas sector, particularly within the Nigerian context